A Systematic Analysis on Organisational Citizenship Behaviour around the World from 2005 to 2025 - Sankar, M.; Chitra, A.; Mahadevan, A.; Nagarajan, S.; Priya, S. Krishna (International Review of Management and Marketing, 2025)
This study examines how research on Organizational Citizenship Behaviour (OCB) has developed globally from 2005 to 2025 and projects its likely direction in 2026. It seeks to identify the most active authors, journals, institutions, and countries, while also highlighting the themes that are shaping current and future OCB research. We conducted a bibliometric analysis of 2,602 publications retrieved from the Scopus database, of which 1,824 met the inclusion criteria following PRISMA guidelines. Analytical techniques such as performance indicators, keyword co-occurrence, bibliographic coupling, and co-authorship mapping were applied using R and VOS Viewer. To extend beyond descriptive analysis, we used a time-series forecasting model in R to predict both the volume of OCB publications and emerging research themes for 2026. The findings show a steady rise in OCB research, with the United States, China, and India contributing the most. Leading publication outlets include the Journal of Business Ethics and the International Journal of Hospitality Management. OCB is most often linked with job satisfaction, organizational commitment, leadership, and justice, while recent studies also explore green HRM, abusive supervision, and work–family conflict. Forecasting suggests that the field will rebound in 2026 with around 114 publications expected, and that employee attitudes, leadership, and organizational support will remain central themes. By combining bibliometric mapping with predictive modelling, this study not only reviews the global state of OCB research but also offers a forward-looking view of where the field is heading. The results provide useful insights for academics and practitioners interested in the evolving role of OCB in organizations.